Memahami Penerapan Akad dan Pengambilan Laba dalam Transaksi Jual Beli di pasar Sesuai Syariat Islam - Lestari, Dinda; Melany, Melany (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Buying and selling transactions are economic activities that are often carried out in life. In the context of Islamic Shari'a, the payment of buying and selling must be balanced with the rate stipulated in Islamic Sharia law. This involves the application of a valid contract (agreement) as well as the taking of fair profits. The purpose of this study is to determine the implementation of contracts and profit taking in the payment of buying and selling in taxes in accordance with Islamic law. In the payment of sharia buying and selling, principles are found that must be followed, such as justice, mutual idling (mutual agreement), and avoiding riba (interest) and gharar (uncertainty). The research method used is a literature study, by collecting data from relevant primary and secondary sources. Data analysis was carried out by comparing various approaches and views of scholars as well as interpretations of Islamic law related to the application of contracts and profit taking in buying and selling transactions. The results of the study prove that the application of a valid contract in sharia buying and selling transactions involves an agreement between the seller and buyer regarding the type of goods, price, and other conditions in accordance with Islamic law. These transactions must be conducted in good faith and do not involve any element of fraud or obscurity. In addition, profit taking in Islamic buying and selling transactions must be fair and not involve usury practices. The profit earned should be a reasonable reward for the effort and risk taken in the transaction.